Recent researches on natural pigments stabilized by clay minerals: A review. (June 2021) - Li, Shue; Mu, Bin; Wang, Xiaowen; Wang, Aiqin
Abstract: Natural pigments from plant sources are often stabilized by several types of protection systems, including incorporation of co-pigment compounds, formation of supramolecular complexes, and encapsulation or loading using nano-carriers. Inspired by Maya blue, clay minerals as a kind of promising nano-carriers are employed to stabilize the natural pigments due to their unique structural characteristics, abundant reserves, cheap and eco-friendly nature. The unique features in the structures and physicochemical properties of clay minerals provide the opportunity to stabilize these natural pigments. This review summarizes the most recent studies and provides the insight into the natural or synthetic clay minerals for enhancing the environmental stability of natural pigments extracted from various fruits, vegetables and flowers. Based on the cognition and accumulation combining reviewing the literatures with our relevant research achievements, several suggestions are proposed for the design and the potential applications of hybrid materials composed of clay mineral and natural pigments. Graphical abstract: Image 1 Highlights: Innate disadvantages of natural pigments severely limited their wide applications. Clay minerals are promising carriers for enhancing the stability of plant pigments. Recent advances on natural plant pigments stabilized by clay minerals are reviewed. Several suggestions are proposed for clay mineral-based organic/inorganic hybrid materials.